DEVELOPING LEARNING MEDIA USING AUDIO VISUAL FOR STUDENTS GRADE VII AT MTS. MIFTAHUL IHSAN - Yuliarsih Yuliarsih (INTERAKSI : Jurnal Kependidikan, 2017)
The English teaching and learning at MTS.Miftahul Ihsan, Sumenep for students grade VII was considered unable to achieve its learning purpose. The main problem was that there was not an appropriate learning media used in the learning activity.So that objective of the development is to produce the appropriate learning media using Audio Visual.The procedures being implied were collecting information using kinesthetic, audio and visual learning style, developing learning media, validation from expert of design and expert of learning content, trying out the learning media through individual experiment, small group experiment and field experiment, revising the learning media, and finally packing the learning media. From the try out, the data showed the applicability of the learning media could motivate the students in learning English. It was reflected in the data collected from the questionnaires and class room observation. The data collected from observation showed that the learning media of using audio visual are appropriate for the students.The final product of the development is learning media using audio visual. The learning media was packed in the form of compact disc. It contains the materials studied for grade VII.